Perancangan Sistem Informasi Desa Gunung Malintang Kecamatan Barumun Tengah Kabupaten Padang Lawas - Siregar, Yusril Izza Haholongan; Muliono, Rizki (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2025)
Systems that are still manual or direct recording that is not in accordance with their function will run for a very long time and take a lot of time, where manual systems still rely heavily on recording that prioritizes accuracy and observation as the main focus in the implementation process. This research aims to design and build a web-based information system to replace the manual recording system used by village officials in Gunung Malintang Village, Central Barumun District, Padang Lawas Regency. The system is designed using the PHP programming language with MySQL database. The system design follows the System Development Life Cycle (SDLC) approach with a waterfall model that includes requirements analysis, design, implementation, and system testing. The results of the study show that the designed information system is able to improve the efficiency of data management, reduce recording errors, and speed up the village administration process. This system not only makes it easier for village officials to manage data, but also provides benefits to the community through faster and more accurate services. With the implementation of this information system, it is hoped that village governance will become more modern and transparent, supporting the improvement of the quality of public services in rural areas.